2019
DOI: 10.17221/139/2018-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, physicochemical properties and antioxidant capacity of bee pollens

Abstract: Six supposedly unifloral bee pollens of various botanical origins were characterised by morphometry, SEM, CIE L*a*b* colour parameters and FTIR spectroscopy. Botanical origin and homogeneity of bee pollens were verified by colour and morphology of pollen grains. Water activity, moisture and antioxidant capacity of bee pollens were also evaluated. The results were discussed in terms of connection between botanical origin, composition and antioxidant properties of pollen materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
10
1
2
Order By: Relevance
“…The FTIR-ATR spectra of pollens belonging to different genera as shown in Figure 2 were only a sample representative of each genus reported. Main constituents of bee pollen are proteins, saccharides and lipids; IR spectra of the pollen samples have similar characteristic peaks [17,18,19], but several peculiarities can be found in dissimilar pollens due to little differences in chemical compositions. The meaningful IR peaks of bee pollens are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FTIR-ATR spectra of pollens belonging to different genera as shown in Figure 2 were only a sample representative of each genus reported. Main constituents of bee pollen are proteins, saccharides and lipids; IR spectra of the pollen samples have similar characteristic peaks [17,18,19], but several peculiarities can be found in dissimilar pollens due to little differences in chemical compositions. The meaningful IR peaks of bee pollens are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Kasprzyk et al in 2018 [18] investigated the floral origin of bee pollens using a sequence of chemometric procedures (DA, HCA, etc.) applied on parameters obtained from FTIR spectra to confirm the floral origin of rape pollen; Svecniak et al in 2015 [20] explored the possible clustering of unifloral honeys belonging to different pollens using principal component analysis; in addition Bleha et al in 2019 [17] characterized six unifloral bee pollens of various botanical origins by morphometry, SEM, CIE L*a*b* color parameters and FTIR spectroscopy. However, in the literature there are no reports on the use of FTIR data together with those of color and granulometry to identify the botanical origin of bee pollen loads.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, statistical evaluation of the image spectra may be useful for the evaluation of bee pollen homogeneity and for the discrimination of bee pollen samples yielding trends and clusters [8,16]. In our previous works [8,9,18,19], vibrational spectroscopy and color analysis based on diffuse reflectance VIS spectra were used in the analysis of homogenates of bee pollen and bee bread; however, this approach is not able to evaluate the botanical and color heterogeneity of these beekeeping products.…”
Section: Introductionmentioning
confidence: 99%
“…Alicic et al 16 and Leja et al 11 reported the action mechanism responsible for antioxidant and antibacterial potential of pollen grains that accompanying with the existence of flavonoids, phenolic acids, and pigments like as β-carotene. Lately, Bleha et al 17 evidenced the antioxidant potential of Bee pollen extracts correlated with high content of polyphenols. The high contents of flavonoids and phenols of Apis mellifera pollen grains represent the main reasons antioxidant activity 18.…”
Section: Introductionmentioning
confidence: 99%